The impact of a private-public partnership delivery system on the HIV continuum of care in a South Indian city. Issue 3 (4th March 2018) - Waldrop, Greer; Sarvode, Suraj; Rao, Srirama; Swamy, V.H.T.; Solomon, Sunil Suhas; Mehta, Shruti H.; Mothi, S. N.
ABSTRACT: We characterized the impact of a Private-Public Partnership (PPP) on the continuum of HIV care (e.g., treatment initiation, ART effectiveness and loss to follow-up) among adults enrolled at a private hospital/ART link center in the southern state of Karnataka, India from 2007 through 2012. Data on 2326 adults in care were compiled using an electronic database supplemented with medical chart abstraction. Survival methods with staggered entries were used to analyze time to ART initiation and loss to follow-up as well as associated factors. Mixed effects linear regression models were used to assess ART effectiveness. The mean age of adults in care was 36 years; 40% were male. The majority were married, had less than primary education, and less than 45 US dollars (3000 Indian Rupee) monthly income. The mean CD4 at presentation was 527 cells/mm 3 . The median time from ART eligibility to initiation was 5 and 2 months for before and after the PPP, respectively ( p  < 0.001). Becoming eligible after PPP was associated with more rapid treatment initiation (Hazard Ratio: [95% Confidence Interval] 1.49 [1.11, 1.99]). Moreover, among the 1639 persons lost to follow-up, more rapid loss was observed before the PPP (12.77 months) vs. after (13.37 months) ( p  = 0.25) and there was a significant interaction between ART status and calendar time before and after the PPP ( p  < 0.001). Being on treatment was associated with a lower likelihood of becoming lost before the PPP (HR: [95% CI] 0.33 [0.27, 0.42]), but this association was reversed after the PPP (HR: [95% CI] 1.77 [1.54, 2.04]), p -value for interaction <0.001. Treatment response measured by CD4 was comparable before and after the PPP ( p  = 0.088). Our findings suggest that PPP models of ART delivery may improve HIV treatment initiation and loss to follow-up without compromising the effectiveness of treatment. Efforts to expand these system-level interventions should be considered with on-going evaluation.